Seismic design and importance factor: Benefit/cost for overall service time versus per unit service time. (January 2016) - Pozos-Estrada, A.; Liu, T.J.; Gomez, R.; Hong, H.P.
Highlights: Assembled a detailed seismic hazard model applicable to a region in Mexico. Estimated uniform hazard spectra for several sites, including Mexico City. Investigated the effect of sigma of attenuation relation on optimum seismic design. Assessed the differences in the optimum seismic return period values for seven locations. Provided basis to select the importance factor based on damage cost information. Abstract: The maximum expected monetary benefit or minimum expected cost rule are often adopted to assess the optimum structural design levels under infrequent large earthquakes. In the assessment, the monetary benefit or cost functions are frequently established by considering the overall benefit or lifecycle cost at present value for a given structural design life. The selection of the structural design life is somewhat arbitrary, and in many cases one is interested in maximizing the structural service time or the benefit per unit service time. The consideration of the benefit (or cost) at present value per lifecycle or per unit service time may lead to different optimum design levels for a given planning time horizon. Moreover, it is unknown if the recommended importance factor in design codes to increase the seismic design load for classes of buildings is optimum. These two issues are investigated through numerical analyses by placing a structure at several different locations in Mexico and considering assembled detailed seismic hazard model. The implication of the results for the codified designs and for selecting the importance factor is discussed.